2018 9th International Symposium on Telecommunications (IST) 2018
DOI: 10.1109/istel.2018.8661064
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Improvement of a Lightweight Anonymous Authentication Protocol for Mobile Pay-TV Systems

Abstract: For many years, the pay-TV system has attracted a lot of users. Users have recently expressed the desire to use mobile TV or mobile payment via anonymous protocols. The mobile users have also received their services over cellular communications networks. Each mobile device receives services from each head end systems. With increasing numbers of users and the expansion of Internet, user's privacy has become crucial important. When a device leaves the head end system's range, it must receive services from anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, Kim and Lee showed that Chen et al's protocol suffers the risks in password guessing attack and impersonation attack and gave an improved version [33]. In 2018, Far and Alagheband also enhanced the security in Chen et al's protocol to alleviate its security risks [15].…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…However, Kim and Lee showed that Chen et al's protocol suffers the risks in password guessing attack and impersonation attack and gave an improved version [33]. In 2018, Far and Alagheband also enhanced the security in Chen et al's protocol to alleviate its security risks [15].…”
Section: Related Workmentioning
confidence: 99%
“…Zhu presented a deniable authentication protocol for pay-TV system based on chaotic maps, which is called DAP-TV [41]. In 2020, [28] Designed an improved version using RSA blind signature technology Wang and Laith [21] 2008 Huang et al [20] Proposed an improved key distribution scheme Sun and Leu [34] 2009 Yang and Chang [31] Designed the first one-to-many authentication scheme Wang and Qin [35] 2012 Sun and Leu [34] Presented an enhanced scheme against impersonation attacks Kim and Lee [33] 2012 Chen et al [32] Gave an improved version against password guessing attack and impersonation attack Arshad et al [36] 2017 Wang and Qin [35] Designed an authentication scheme without bilinear pairings Far and Alagheband [15] 2018 Chen et al [32] Proposed a strengthened scheme to alleviate its security risks 3 Wireless Communications and Mobile Computing Kumaravelu et al [14] designed an anonymous scheme which can authenticate both users and HES, with low computational cost.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations